A ratiometric fluorescence-scattering sensor for rapid, sensitive and selective detection of doxycycline in animal foodstuffs. (30th March 2022) - Ding, Lu; Cao, Yatian; Li, Huihui; Wang, Fuxiang; Guo, Dong-Yu; Yang, Weiting; Pan, Qinhe
Graphical abstract: Highlights: ZIF-8 and BSA were elaborately designed as a ratiometric sensor for doxycycline. The sensor coupled the fluorescence signal and the second-order scattering signal. The sensor possessed rapid response, superior sensitivity and excellent selectivity. The sensor was applied to the analysis of doxycycline in basa fish and pure milk. Abstract: The residue problem of tetracycline antibiotics, especially doxycycline (DC), in animal foodstuffs has attracted much attention. This paper reported ZIF-8 and bovine serum albumin (BSA) as a ratiometric fluorescence-scattering sensor for DC. The mechanism relied on the disassembly of ZIF-8 caused by DC, bringing weakened second-order scattering, and the double fluorescence amplification of DC under ZIF-8 with BSA, inducing enhanced fluorescence. The response of the sensor was completed within 1 min, and the detection limit for DC (3.4 nM) was 1–2 orders of magnitude lower than the reported ones. The distinguishment of DC from other tetracycline antibiotics was also achieved by the sensor. The sensor was applied to detecting DC in animal foodstuffs with satisfactory recoveries (80.0–104.0%). Hence, this work develops a rapid, sensitive and selective ratiometric sensor to monitor the DC residue in animal foodstuffs, also opens the window to construct ratiometric DC sensors with the fluorescence-scattering strategy.